Analisis Pendapatan Agroindustri Manisan Carica Sebelum dan Saat Pandemi Covid-19 di Kabupaten Wonosobo - Fivintari, Francy Risvansuna; Safitri, Rekhanna Zahra Jelang; Istiyanti, Eni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agroindustry processed carica fruit in the Wonosobo district is one of the businesses by untilizing potential agricultural produce, but with the case of covid-19 in 2020 led to a decrease in sales and reduction in production. The study aims to: (1) determine the difference on the cost, income, and profit of the carica sweet agroindusrty before and during the Covid-19 pandemic in Wonosobo Regency; (2) and determine the feasibility of the carica sweet agroindustry in Wonosobo Regency. Sampling was using census method consist of 30 craftsmen. This research was conducted in Wonosobo Regency, especially at Kejajar District and Wonosobo District. The results showed that the average cost incurred for the carica sweet agroindustry in one week of production before the pandemic amounted to Rp8,920,289 and the pandemic amounted to Rp4,620,202; the average income incurred for the carica sweet agroindustry before the pandemic amounted to Rp10,391,109 and the current pandemic amounted to Rp6,785,86; the average profit spent for the carica sweet agroindustry before the pandemic amounted to Rp10,166,378 and the pandemic time of Rp6,545,631. The carica sweet agroindustry in Wonosobo Regency is worth the effort to be seen from the value of R/C ratio more than 1 had 2.1 before pandemic and 2.4 for pandemic; the capital productivity had reached 117% before pandemic and 150% for pandemic.